The Islamic financial literacy and market discipline: Does gender have the moderating role? - Widyastuti, Umi; Soma, Abdul Mukti (Jurnal Keuangan dan Perbankan, 2023)
This study contributes to examine the effect of Islamic financial literacy on market discipline and to confirm whether gender can employ as moderating variable in this model. The primary data was collected from 93 academicians who invest in Sharia mutual funds. Based on the data analysis, this study proved that there is a positive impact of Islamic financial literacy on investment’s withdrawal behaviour which indicated the market discipline. Moreover, a multi group analysis results that Islamic financial literacy has higher influence for female Sharia mutual fund’s investors in withdrawing their investments. But, the influence of Islamic financial literacy on market discipline among gender is not significantly different, therefore gender could not employ as a moderating variable in this model.JEL: G2, G23